2018
DOI: 10.18632/oncotarget.24786
|View full text |Cite
|
Sign up to set email alerts
|

Sulforaphane suppresses oral cancer cell migration by regulating cathepsin S expression

Abstract: Sulforaphane has been demonstrated to exert numerous biological effects, such as neuroprotective, anti-inflammatory, and anticancer effects. However, the detailed effects of sulforaphane on human oral cancer cell migration and the underlying mechanisms remain unclear. In this study, we observed that sulforaphane attenuated SCC-9 and SCC-14 cell motility and invasiveness by reducing cathepsin S expression. Moreover, sulforaphane increased microtubule-associated protein 1 light chain 3 (LC3) conversion, and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 49 publications
1
8
0
Order By: Relevance
“…Thus, these studies emphasized the role of ADAM9 in various cancers and highlighted the association of ADAM9 with a poor RCC prognosis. However, the current study showed that sulforaphane or hispolon could similarly activate autophagy and suppress the invasion and metastasis of oral cancer cells or cervical cancer cells by downregulating CTSS through the upregulation of the MEK/ERK signaling pathway [42,43]. Consistent with the above studies, we were able to demonstrate that fisetin inhibited the metastatic ability of human RCC cells through the activation of the MEK/ERK pathways involved in CTSS/ADAM9 expression.…”
Section: Discussionsupporting
confidence: 87%
“…Thus, these studies emphasized the role of ADAM9 in various cancers and highlighted the association of ADAM9 with a poor RCC prognosis. However, the current study showed that sulforaphane or hispolon could similarly activate autophagy and suppress the invasion and metastasis of oral cancer cells or cervical cancer cells by downregulating CTSS through the upregulation of the MEK/ERK signaling pathway [42,43]. Consistent with the above studies, we were able to demonstrate that fisetin inhibited the metastatic ability of human RCC cells through the activation of the MEK/ERK pathways involved in CTSS/ADAM9 expression.…”
Section: Discussionsupporting
confidence: 87%
“…ERK activation prevents cancer cell apoptosis [41]. Furthermore, the activation of the ERK/MAPK pathways is also involved in the regulation of LC3 and cathepsin S proteins and is potentially associated with cell autophagy and metastasis in oral cancer cells [42]. Therefore, MAPK proteins are implicated in numerous processes in cancer progression and are therefore worthy of further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…This last activity would be mediated by upregulation of two genes, heme oxygenase 1 ( HMOX1 ) and heat shock protein family A (Hsp70) member 1A ( HSPA1A ), as well as the MICA/B ligand of a natural killer cell activator protein, NKG2D [ 108 ]. In addition, SFN interferes with cell migration, downregulates cathepsin S expression through the ERK signaling pathway, and upregulates microtubule-associated protein 1A/1B-light chain 3 (LC3) [ 109 ].…”
Section: Other Antioxidants With Potential Epigenetic Effect On Squamous Cell Carcinoma Of the Head And Neckmentioning
confidence: 99%